The Treatment of In-Hospital COVID-19 Patient: A Literature Review - Maharani, Ratu; Hidayati , Titiek (Universitas Muhammadiyah Yogyakarta, 2023)
COVID-19 is a disease caused by SARS-CoV-2. This virus attacks the respiratory system and was first discovered in December 2019 in Wuhan, China. This virus spread quickly until WHO declared Covid-19 a global pandemic. Since then, various guidelines on the management of Covid-19 have been published, one of which is the guideline for the management of patients with confirmed Covid-19. Treatment recommendations in various guidelines that have been published are based on expert opinion and some scientific evidence. However, no pharmacological management of COVID-19 has been conclusively agreed upon and most recommendations rely on supportive treatment. Most drugs used in national guidelines have not been well studied against Covid-19 infection due to their nature, situation and novelty. Here, we investigate further the description of the management of Covid-19 patients who are hospitalized in the hospital. The purpose of this literature review is to describe the management of inpatient Covid-19 patients at the hospital and the final results obtained from each administration of therapy. Literature study was carried out by searching literature in the form of articles and journals in national and international e-databases using the keywords management, inpatients, and Covid-19. The results showed that there were pharmacological treatments in the form of antivirals, antibiotics, vitamins and symptomatic drugs, as well as non-pharmacological treatments in the form of administering oxygen to hospitalized Covid-19 patients. Given the rapid updating of information regarding Covid-19, it is hoped that this study can facilitate information regarding the management of Covid-19.